Front Cover Picture: Semi‐Rational Engineering of Toluene Dioxygenase from Pseudomonas putida F1 towards Oxyfunctionalization of Bicyclic Aromatics (Adv. Synth. Catal. 21/2021). Issue 21 (13th May 2021) - Wissner, Julian L.; Schelle, Jona T.; Escobedo‐Hinojosa, Wendy; Vogel, Andreas; Hauer, Bernhard
Abstract : The front cover picture, designed and donated by WesWizzArt and painted by the Mexican artist Way (Wayra Castillo‐Guerrero), illustrates the toluene dioxygenase‐catalyzed conversion of aromatics. The enzyme exhibits a high affinity for monocyclic, but only a low one for bicyclic substrates. A semi‐rational designed mutant library opened the way for the conversion of the bicyclic substrates naphthalene, 1, 2, 3, 4‐tetrahydroquinoline and 2‐phenylpyridine at unprecedented rates, enabling the biosynthesis of their products in substantial quantities. Variants at active site positions M220, A223 and F366 exhibited a major influence in product formation and selectivity. Details can be found in the Research Article by Bernhard Hauer and co‐workers (J. L. Wissner, J. T. Schelle, W. Escobedo‐Hinojosa, A. Vogel, B. Hauer, Adv. Synth. Catal . 2021, 363, 4905–4914; DOI: 10.1002/adsc.202100296 ).